Understanding government Web communication strategy as applied within the Public Health Agency of Canada - Knazko, Jana (University of Ottawa (Canada), 2008)
The research examines the components that make up the Web communication strategy of the Public Health Agency of Canada (PHAC). The thesis focuses on the extent to which PHAC's Web site reflects its mandate and implements the Government of Canada's public policies that regulate its Web presence. The Web communication strategy is analyzed from the perspective of Johnson's conceptualization model which separates a discourse into the stages of production, text, and context. The methodology employs content analysis and interviews to illustrate to which extent the democratic rights of the public were taken into account when the Web strategy was elaborated and how the public and PHAC stakeholders benefit from the implementation of this strategy. The research finds that although the general public is considered to be an important audience segment of the PHAC Web site, the emphasis of Web policy is to reinforce health care, education, and government sector stakeholder relationships. Keywords. public health agency, health Web site, Web analytics, communications policy, e-communications, accessibility, stakeholders, government Web.
Keywords: Health Sciences, Public Health.; Political Science, Public Administration.; Information Science.